Assessment of railway earthworks using DAS based active MASW surveys - Muhammad Saqlain; Andrew Trafford; Qasim Khan; Ben Dashwood; Jonathan E. Chambers; Gavin Jessamy; Julian Harms; Shane Donohue (Transportation Geotechnics, 2026)

Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Correction: Carcinogenic and non-carcinogenic risk assessment of heavy metals in PM2.5 air pollutant in Ulaanbaatar, Mongolia during the wintertime - Odbaatar Enkhjargal; Munkhnasan Lamchin; Xue Yi You; Jonathan Chambers; Davaagatan Tuyagerel; Renchinmyadag Tovuudorj; Zolzaya Khurelsukh; Enkhmaa Sarangerel; Nyamgerel Enkhtuya (Air Quality, Atmosphere & Health, 2025)

Carcinogenic and non-carcinogenic risk assessment of heavy metals in PM2.5 air pollutant in Ulaanbaatar, Mongolia during the wintertime - Odbaatar Enkhjargal; Munkhnasan Lamchin; Xue Yi You; Jonathan Chambers; Davaagatan Tuyagerel; Renchinmyadag Tovuudorj; Zolzaya Khurelsukh; Enkhmaa Sarangerel; Nyamgerel Enkhtuya (Air Quality, Atmosphere & Health, 2025)

Four years of landslide observation with anthropogenic loading as an additional trigger - Analysis of seasonal and annual variability of physical parameters - Artur Marciniak; Sebastian Kowalczyk; Szymon Oryński; Justyna Cader; Jonathan Chambers; Iwona Stan-Kłeczek; Mariusz Majdański (Engineering Geology, 2024)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Corrigendum to “Four-dimensional electrical resistivity imaging for monitoring pumping-induced saltwater intrusion in a coastal aquifer” [Sci. Total Environ. Volume 867 (2023) 161442] - Mark C. McDonnell; Raymond Flynn; Jesús Fernández Águila; Gerard A. Hamill; Shane Donohue; Eric M. Benner; Christopher Thomson; Georgios Etsias; Thomas S.L. Rowan; Paul B. Wilkinson; Philip I. Meldrum; Jonathan E. Chambers (Science of The Total Environment, 2024)

Practical considerations for using petrophysics and geoelectrical methods on clay rich landslides - James P. Boyd; Andrew Binley; Paul Wilkinson; Jessica Holmes; Edward Bruce; Jonathan Chambers (Engineering Geology, 2024)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Assessing the risk of slope failure to highway infrastructure using automated time-lapse electrical resistivity tomography monitoring - Jim Whiteley; Cornelia Inauen; Paul Wilkinson; Philip Meldrum; Russell Swift; Oliver Kuras; Jonathan Chambers (Transportation Geotechnics, 2023)

Space heating demand in the office building stock: Element-based bottom-up archetype model - Francesco Sasso; Jonathan Chambers; Martin K. Patel (Energy and Buildings, 2023)

Assessment of the thermal energy flexibility of residential buildings with heat pumps under various electric tariff designs - Eric John Wilczynski; Jonathan Chambers; Martin K. Patel; Ernst Worrell; Simon Pezzutto (Energy and Buildings, 2023)

Combined electrical resistivity tomography and ground penetrating radar to map Eurasian badger (Meles Meles) burrows in clay-rich flood embankments (levees) - Adrian White; Paul Wilkinson; James Boyd; James Wookey; John Michael Kendall; Andrew Binley; Timothy Grossey; Jonathan Chambers (Engineering Geology, 2023)

Improving data collection in pregnancy safety studies: Towards standardization of data elements in pregnancy reports from public and private partners (ConcePTION) - Guillaume Favre; Jonathan L. Richardson; Alan Moore; Yvonne Geissbühler; Valentine Jehl; Alison Oliver; Svetlana Shechtman; Orna Diav-Citrin; Maya Berlin; Tal De-Haan; Anil Mor; Meritxell Sabidó; et al. (Neurotoxicology and Teratology, 2023)

Expert consensus on neurodevelopmental outcomes in pregnancy pharmacovigilance studies - Rebecca Bromley; Miriam Bickle Graz; Matthew Bluett-Duncan; Christina Chambers; Per Damkier; Kim Dietrich; Helen Dolk; Kimberley Grant; Sarah Mattson; Kim Meador; Hedvig Nordeng; Tim Oberlander; et al. (Neurotoxicology and Teratology, 2023)

4D electrical resistivity to monitor unstable slopes in mountainous tropical regions: an example from Munnar, India - Arnaud Watlet; Hemalatha Thirugnanam; Balmukund Singh; Nitin Kumar M.; Deepak Brahmanandan; Cornelia Inauen; Russell Swift; Phil Meldrum; Sebastian Uhlemann; Paul Wilkinson; Jonathan Chambers; Maneesha Vinodini Ramesh (Landslides, 2023)
The number of large landslides in India has risen in the recent years, due to an increased occurrence of extreme monsoon rainfall events. There is an urgent need to improve our understanding of moisture-induced landslide dynamics, which vary both spatially and temporally. Geophysical methods provide integrated tools to monitor subsurface hydrological processes in unstable slopes at high spatial resolution. They are complementary to more conventional approaches using networks of point sensors, which can provide high temporal resolution information but are severely limited in terms of spatial resolution. Here, we present and discuss data from an electrical resistivity tomography monitoring system—called PRIME—deployed at the Amrita Landslide Early Warning System (Amrita-LEWS) site located in Munnar in the Western Ghats (Kerala, India). The system monitors changes in electrical resistivity in the subsurface of a landslide-prone slope that directly threatens a local community. The monitoring system provides a 4D resistivity model informing on the moisture dynamics in the subsurface of the slope. Results from a 10-month period spanning from pre-monsoon to the end of the monsoon season 2019 are presented and discussed with regard to the spatial variation of soil moisture. The temporal changes in resistivity within the slope are further investigated through the use of time-series clustering and compared to weather and subsurface pore water pressure data. This study sheds new light on the hydrological processes occurring in the shallow subsurface during the monsoon and potentially leading to slope failure. This geophysical approach aims at better understanding and forecasting slope failure to reduce the risk for the local community, thereby providing a powerful tool to be included in local landslide early warning systems.

A Review on Applications of Time-Lapse Electrical Resistivity Tomography Over the Last 30 Years : Perspectives for Mining Waste Monitoring - Adrien Dimech; LiZhen Cheng; Michel Chouteau; Jonathan Chambers; Sebastian Uhlemann; Paul Wilkinson; Philip Meldrum; Benjamin Mary; Gabriel Fabien-Ouellet; Anne Isabelle (Surveys in Geophysics, 2022)
Mining operations generate large amounts of wastes which are usually stored into large-scale storage facilities which pose major environmental concerns and must be properly monitored to manage the risk of catastrophic failures and also to control the generation of contaminated mine drainage. In this context, non-invasive monitoring techniques such as time-lapse electrical resistivity tomography (TL-ERT) are promising since they provide large-scale subsurface information that complements surface observations (walkover, aerial photogrammetry or remote sensing) and traditional monitoring tools, which often sample a tiny proportion of the mining waste storage facilities. The purposes of this review are as follows: (i) to understand the current state of research on TL-ERT for various applications; (ii) to create a reference library for future research on TL-ERT and geoelectrical monitoring mining waste; and (iii) to identify promising areas of development and future research needs on this issue according to our experience. This review describes the theoretical basis of geoelectrical monitoring and provides an overview of TL-ERT applications and developments over the last 30 years from a database of over 650 case studies, not limited to mining operations (e.g., landslide, permafrost). In particular, the review focuses on the applications of ERT for mining waste characterization and monitoring and a database of 150 case studies is used to identify promising applications for long-term autonomous geoelectrical monitoring of the geotechnical and geochemical stability of mining wastes. Potential challenges that could emerge from a broader adoption of TL-ERT monitoring for mining wastes are discussed. The review also considers recent advances in instrumentation, data acquisition, processing and interpretation for long-term monitoring and draws future research perspectives and promising avenues which could help improve the design and accuracy of future geoelectric monitoring programs in mining wastes.

Estimation of bioclimatic variables of Mongolia derived from remote sensing data - Munkhdulam Otgonbayar; Clement Atzberger; Erdenesukh Sumiya; Sainbayar Dalantai; Jonathan Chambers (Frontiers of Earth Science, 2022)

A linked geomorphological and geophysical modelling methodology applied to an active landslide - Jimmy Boyd; Jonathan Chambers; Paul Wilkinson; Maria Peppa; Arnaud Watlet; Matt Kirkham; Lee Jones; Russel Swift; Phil Meldrum; Sebastian Uhlemann; Andrew Binley (Landslides, 2021)
Moisture-induced landslides are a global geohazard; mitigating the risk posed by landslides requires an understanding of the hydrological and geological conditions present within a given slope. Recently, numerous geophysical studies have been attempted to characterise slow-moving landslides, with an emphasis on developing geoelectrical methods as a hydrological monitoring tool. However, landslides pose specific challenges for processing geoelectrical data in long-term monitoring contexts as the sensor arrays can move with slope movements. Here we present an approach for processing long-term (over 8 years) geoelectrical monitoring data from an active slow-moving landslide, Hollin Hill, situated in Lias rocks in the southern Howardian Hills, UK. These slope movements distorted the initial setup of the monitoring array and need to be incorporated into a time-lapse resistivity processing workflow to avoid imaging artefacts. We retrospectively sourced seven digital terrain models to inform the topography of our imaging volumes, which were acquired by either Unmanned Aerial Vehicle (UAV)-based photogrammetry or terrestrial laser ranging systems. An irregular grid of wooden pegs was periodically surveyed with a global position system, from which distortions to the terrain model and electrode positions can be modelled with thin plate splines. In order to effectively model the time-series electrical resistivity images, a baseline constraint is applied within the inversion scheme; the result of the study is a time-lapse series of resistivity volumes which also incorporate slope movements. The workflow presented here should be adaptable for other studies focussed on geophysical/geotechnical monitoring of unstable slopes.

Global and cross-country analysis of exposure of vulnerable populations to heatwaves from 1980 to 2018 - Jonathan Chambers (Climatic Change, 2020)
Heatwaves have become more frequent and intense due to anthropogenic global warming and have serious and potentially life-threatening impacts on human health, particularly for people over 65 years old. While a range of studies examine heatwave exposures, few cover the whole globe and very few cover key areas in Africa, South America, and East Asia. By using global gridded climate reanalysis, population, and demographic data, this work analyses trends in change in exposure of vulnerable populations to heatwaves, providing global and per-country aggregate statistics. The difference between the global mean of heatwave indexes and the mean weighted by vulnerable population found that these populations are experiencing up to five times the number of heatwave days relative to the global average. The total exposures, measured in person-days of heatwave, highlight the combined effect of increased heatwaves and aging populations. In China and India, heatwave exposure increased by an average of 508 million person-days per year in the last decade. Mapping of changes per country highlighted significant exposure increases, particularly in the Middle East and in South East Asia. Major disparities were found between the heatwave exposures, country income group, and country health system capacity, thus highlighting the significant inequalities in global warming impacts and response capacities with respect to health across countries. It is therefore of prime importance that health development and response are coordinated with climate change mitigation and adaptation work.

Mapping pasture biomass in Mongolia using Partial Least Squares, Random Forest regression and Landsat 8 imagery - Munkhdulam Otgonbayar; Clement Atzberger; Jonathan Chambers; Amarsaikhan Damdinsuren (International Journal of Remote Sensing, 2019)

Ertapenem for osteoarticular infections in obese patients: a pharmacokinetic study of plasma and bone concentrations - Jonathan Chambers; Madhu Page-Sharp; Sam Salman; John Dyer; Timothy M. E. Davis; Kevin T. Batty; Laurens Manning (European Journal of Clinical Pharmacology, 2019)

Dating prehistoric bog‐fires in northern England to calendar years by long‐distance cross‐matching of pine chronologies - Frank M. Chambers; Jonathan G. A. Lageard; Gretel Boswijk; Peter A. Thomas; Kevin J. Edwards; Jennifer Hillam (Journal of Quaternary Science, 1997)

Dating prehistoric bog-fires in northern England to calendar years by long-distance cross-matching of pine chronologies - Frank M. Chambers; Jonathan G. A. Lageard; Gretel Boswijk; Peter A. Thomas; Kevin J. Edwards; Jennifer Hillam (Journal of Quaternary Science, 1997)